PID Controller Tuning via Dominant Pole Placement in Comparison with Ziegler-Nichols Tuning. Issue 18 (2019) - Fišer, Jaromír; Zítek, Pavel
Abstract: The paper provides PID controller tuning for the third-order plants with delay. For obtaining the PID setting the dominant three-pole placement is applied to achieve desired dynamics. This dynamics is proposed such that to overcome well-known Ziegler-Nichols (Z-N) tuning rule. The desired dynamics proposal is found out by the integrated absolute error (IAE) optimization of the fourth-order PID control loop with delay. The initial guess for this optimization is based on ultimate frequency assessment and the IAE optimization is performed with respect to disturbance rejection. The dominant three-pole placement approach to the PID tuning is designed for oscillatory, aperiodic and integrating plants of the third-order. On examples the proposed PID tuning is demonstrated overcoming the Z-N tuning.